Improving the mechanism for financing small businesses and private entrepreneurship (Global Scientific Review, 2024)
Private entrepreneurship is developing rapidly in Uzbekistan. A number of favorable legal and economic conditions have been created for domestic entrepreneurs and investors. The national economy continues the process of liberalization, which has a positive impact on the growth of economic indicators. Successful economic development creates conditions for the growth of the population's well-being. Measures are being implemented to further improve the business environment and the development of entrepreneurship. The article presents the results of the analysis and prospects for the development of private entrepreneurship. It also priority directions of further development of the private sector are analyzed